How self-stigma affects patient activation in persons with type 2 diabetes: a cross-sectional study. Issue 5 (17th May 2020) - Kato, Asuka; Fujimaki, Yuko; Fujimori, Shin; Isogawa, Akihiro; Onishi, Yukiko; Suzuki, Ryo; Ueki, Kohjiro; Yamauchi, Toshimasa; Kadowaki, Takashi; Hashimoto, Hideki
Abstract : Objectives: Self-stigma is associated with lower patient activation levels for self-care in persons with type 2 diabetes mellitus (T2DM). However, the causal pathway linking self-stigma with patient activation for self-care has not been shown. In order to determine how self-stigma affects patient activation for self-care, we tested a two-path hypothetical model both directly and as mediated by self-esteem and self-efficacy. Design: A cross-sectional study. Setting: Two university hospitals, one general hospital and one clinic in Japan. Participants: T2DM outpatients receiving treatment (n=209) completed a self-administered questionnaire comprising the Self-Stigma Scale, Patient Activation Measure, Rosenberg Self-Esteem Scale, General Self-Efficacy Scale, Patient Health Questionnaire, haemoglobin A1c test, age, sex and body mass index. Primary and secondary outcome measures: Self-stigma levels were measured by using the Self-Stigma Scale. Patient activation levels were measured by the Patient Activation Measure. Results: Path analysis showed a strong relationship between self-stigma and patient activation (χ 2 =27.55, p=0.120; goodness-of-fit index=0.97; adjusted goodness-of-fit index=0.94; comparative fit index=0.98; root mean square error of approximation=0.04). Self-stigma had a direct effect on patient activation (β=−0.20; p=0.002). Indirectly, self-stigma affected patient activation along two paths (β=0.31; p<0.001) by reducing self-esteem (β=−0.22; p<0.001) and self-efficacy (β=−0.36; p<0.001). Conclusions: Due to the cross-sectional design of the study, longitudinal changes between all the variables cannot be established. However, the findings indicate that self-stigma affected patient activation for self-care, both directly and as mediated by self-esteem and self-efficacy. Interventions that increase self-esteem and self-efficacy may decrease self-stigma in patients with T2DM, thus increasing patient activation for self-care.